Could our epistemic reasons be collective practical reasons? (Nous (0029-4624), 2021)
Are epistemic reasons merely a species of instrumental practical reasons, making epistemic rationality a specialized form of instrumental practical rationality? Or are epistemic reasons importantly different in kind? Despite the attractions of the former view, Kelly (2003) argues quite compellingly that epistemic rationality cannot be merely a matter of taking effective means to one's epistemic ends. I argue here that Kelly's objections can be sidestepped if we understand epistemic reasons as instrumental reasons that arise in light of the aims held by social collectives of which we are members, rather than being fixed by our own individual goals. This social version of epistemic instrumentalism would not be subject to counterexamples that point to the failure of individual people to possess desires or goals that would account for all of the epistemic reasons we find it natural to attribute to them. I conclude by comparing the proposed view to the alternative version of instrumentalism defended by Kornblith (1993). I argue that the social view I sketch here has one noteworthy advantage. It better accounts for the intuitive distinctness of our practical and epistemic reasons for belief in cases where flouting epistemic norms would better help us to achieve our own individual goals.